PENINGKATAN KEMAMPUAN BERBICARA MENGGUNAKAN MEDIA PERMAINAN ULAR TANGGA DAN MEMAHAMI BERBAGAI BENTUK ENERGI (IPA) DENGAN METODE EKSPRIMEN SISWA KELAS IV SDN JERUK SOKSOK 1 KECAMATAN BINAKAL: SDN JERUK SOKSOK 1 KECAMATAN BINAKAL - MUHLAS HUMAIDI (Dewan Pendidikan Bondowoso, 2023)
This study aims to improve speaking skills and understanding of various forms of energy through the use of snakes and ladders game media and experimental methods in fourth grade students at SDN Jeruk Soksok 1 Binakal District. This research was conducted using a quantitative approach with experimental research methods pre-test post-test control group design. The research sample consisted of two classes, namely the experimental class that used the snakes and ladders game media and the experimental method, and the control class that did not use the snakes and ladders game media and the experimental method. The instruments used in this study were tests of speaking ability and understanding of energy forms. The results showed that the use of snakes and ladders game media and experimental methods can improve speaking skills and understanding of energy forms in fourth grade students at SDN Jeruk Soksok 1 Binakal District. In conclusion, the use of snakes and ladders game media and experimental methods can be an effective alternative in improving students' speaking skills and understanding of energy forms in science subjects in grade fourth grade of SD.